Digital image segmentation procedure as an example of an NP-problem - Lyubchenko, V.; Veretelnyk, K.; Kots, P.; Lyashenko, V. (My University, 2024)
Digital images are a source of additional information about the world around us. Such a source plays an important role in the process of medical diagnosis and research into human health. Digital imaging allows you to obtain the necessary information remotely without additional interference in human life. This can be done using various digital image processing and analysis techniques. However, these methods are typically an NP-problem. The paper discusses the procedure for segmenting medical digital images. The criteria are shown to achieve the required solution when segmenting an image as an NP-problem.
Keywords: Segmentation; Analysis; NP-problem